Greek and Latin Affixes and The Generation Effect - Joseph Scott Oliphant (International Conference on Education and Language (ICEL), 2013)
This action research study was conducted in 2012 at a private high school in Antalya, Turkey.  The research focus was on Greek and Latin affixes and vocabulary along with the robust vocabulary discovery- the generation effect.  The results of the study were significant in terms of recall and the application methodology.  This paper is an abbreviated version of the complete study.  The paper discussesbackground, literature review and cultural factors unique to Turkey.  The project testing and data collection involved academic quiz bowls, unique classroom instruction, a survey, and visual mapping tools.  The paper ends with limitations and areas of future study.